The Concept of God in the Perspectives of Karen Armstrong and Ibn ‘Athaillah al-Sakandari: A Spiritual Historical Comparative Study - Hasanah, Aan (Abrahamic Religions: Jurnal Studi Agama-Agama, 2026)
This study aims to examine and compare the concept of God in the perspectives of Karen Armstrong and Ibn ‘Ata’illah al-Sakandari through a spiritual-historical comparative approach. The research employs a qualitative method with a library research design, focusing on an analysis of the main works of both thinkers. The findings reveal that Karen Armstrong understands God as a transcendent, unique, and incomparable reality that cannot be fully explained through rational concepts, but must be experienced existentially through spiritual awareness, myth, and ethical sensitivity, particularly compassion for the poor and the suffering. In contrast, Ibn ‘Ata’illah al-Sakandari conceives God through the concept of ma‘rifatullah (gnosis of God), which emphasizes inner knowledge attained through divine light, purification of the heart, remembrance (dhikr), trust in God (tawakkul), and a spiritual journey that requires detachment from worldly desires and a deep longing for closeness to Allah. The study concludes that both figures share similarities and differences in their understanding of God. The similarity lies in their view of God as the highest, transcendent reality, incomparable to anything else. The difference lies in the spiritual path toward God: Armstrong emphasizes transcendence, symbolic experience, and ethical-historical consciousness, while Ibn ‘Ata’illah emphasizes practical Sufism through ma‘rifah, spiritual discipline, inner purification, and intimate proximity to God